PIERCE1: a determinant of left-right asymmetry in mammals - Farley, H (2019)
The study of mice with heart and situs defects can provide useful models for improving our understanding of congenital heart defects in humans. This project characterised the involvement of 1700007K13Rik (PIERCE1) in left-right patterning. A proportion of homozygotes with a mutation in this gene were identified by the International Mouse Phenotyping Consortium as exhibiting situs inversus totalis and heart defects, which are indicative of faulty left-right patterning. We hypothesised that this gene is involved in the establishment of ciliary motility at the embryonic node. Motile cilia are also found in the trachea, and if the tracheal cilia of knock-out mice also have motility defects, C9orf116 (the human orthologue of 1700007K13Rik) may be a new candidate gene for primary ciliary dyskinesia, a heterogeneous recessive condition. The evaluation of nodal ciliary motility and nodal flow in mice homozygous for a Pierce1-null allele demonstrated that aberrant motility, leading to a lack of effective leftwards nodal flow, underlies the left-right patterning defects in these mice. In addition to this, studies of tracheal ciliary and sperm flagellar motility showed that PIERCE1 is required for correct motility in all classes of motile cilia and flagellar evaluated. Transmission electron microscopy studies point towards a role for PIERCE1 in the assembly or trafficking of dynein arms and their components; however, protein interaction studies have proved inconclusive thus far at placing PIERCE1 within the network of known dynein arm assembly factors.